(3TQM (B"(3GdESJKfGA(B"s - (3eMeO Hf NdjaI GdehShjs; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s
(3ChdgG (B:s
(3CeG HYO, ajbhd GdYHO Ef gPg cdeGJ TQjaI hJMbjbGJ fajSI TQMJ HgG cdGe GdYGde s
(3BNQgG (B:s
(3dh cGfJ HeKGHI JSYI de jSJbe age gPg GdeYGfj GdKGdKI efgG hCjVkG Ef CQGO Hbhdg GdeLehY s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B223 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B130s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B160 s
Keywords: (3GdfMhs